Biofortification of different maize cultivars with zinc, iron and selenium by foliar fertilizer applications - Xue, Yan-Fang; Li, Xiao-Jing; Yan, Wei; Miao, Qi; Zhang, Chun-Yan; Huang, Meng; Sun, Jin-Bian; Qi, Shi-Jun; Ding, Zhao-Hua; Cui, Zhen-Ling (Frontiers in Plant Science, 2023)
Fertilizer-based biofortification is a strategy for combating worldwide malnutrition of zinc (Zn), iron (Fe) and selenium (Se). Field experiments were conducted to investigate the effects of foliar treatments on concentrations of Zn, Fe, Se, N and bioavailability of Zn and Fe in grains of three maize cultivars grown at three locations. We compared the efficacy of ZnO nanoparticles (ZnO-NPs), Zn complexed chitosan nanoparticles (Zn-CNPs), ZnSO4 and a cocktail solution (containing Zn, Fe and Se). All treatments were foliar-applied at rate of 452 mg Zn L -1, plus urea. Applying ten-fold less Zn plus urea in the form of ZnO-NPs, Zn-CNPs, or ZnSO4 resulted in no increase, or a negligible increase, in grain Zn concentration compared with deionized water. By contrast, among the different Zn sources plus urea applied by foliar sprays, conventional ZnSO4 was the most efficient in improving grain Zn concentration. Furthermore, foliar application of a cocktail solution effectively improved grain concentrations of Zn, Fe, Se and N simultaneously, without a grain yield trade-off. For example, the average grain concentrations were simultaneously increased from 13.8 to 22.1 mg kg -1 for Zn, from 17.2 to 22.1 mg kg -1 for Fe, from 21.4 to 413.5 ug kg -1 for Se and from 13.8 to 14.7 g kg -1 for N by foliar application of a cocktail solution. Because grain yield was significantly negatively correlated with grain nutrient concentrations, the magnitude of increase in grain concentrations of Zn and Fe was most pronounced in maize cultivar with the lowest grain yield. Foliar application of a cocktail solution also significantly decreased phytic acid (PA) concentration, ratios of PA/Fe and PA/Zn in grains, indicating an increased bioavailability of Fe and Zn for human health. In conclusion, we found that foliar application of a cocktail solution including Zn, Fe, Se and N was most effective for biofortification, but that the grains with the lowest yield contained the greatest concentration of these elements. This finding highlights the need to breed maize varieties that are capable of achieving both high grain yield and high grain nutritional quality to address food security and human health challenges.